Determinants of Nurse Performance in Implementation of Infection Prevention and Control Using Employee Engagement Theory in Pandemic Period: A Literature Review - Dewi, Putu Sundari; Suyasa, I Gede Putu Darma; Darmini, AAA Yuliati; Wulandari, Sarah K. (Babali Nursing Research, 2023)
Nurse performance is an important parameter in improving the quality of health services. Nurse performance is influenced by several factors such as individual factors, psychological and organizational factors. The need for support for nurse performance can also be increased through an employee engagement approach. This study aims to identify the determinants factors of nurse performance in implementing infection prevention and control using the theory of employee engagement during a pandemic. This study uses the literature review method. Article search uses 4 journal databases from 2019-2023 which were reviewed including Garuda, Google Scholar, Pubmed and Scient Direct and fifteen articles met the criteria. The results showed that the determinants of nurse performance using employee engagement theory were leadership and organization. Nurse performance influences employee engagement, engaged nurses will have high work engagement and nurses who are not engaged will have low work engagement. The implementation of employee engagement during the pandemic there were still several factors that had not been widely intervened, so further research is needed to find out how the theory of employee engagement is applied to find out the performance factors of nurses in implementing infection prevention and control.